Relevansi Pemikiran Abad Klasik dan Pertengahan: Telaah Pragmatisme dan Skolatisisme dalam Pendidikan Islam - Muhammad Arham; Ilzam Hubby Dzikrillah Alfani (Bustanul Ulum Journal of Islamic Education, 2025)
The background of this research wants to look deeper between education based on experience (pragmatism) and education that is considered traditional based on theory and deductive logic (scholatism). This research aims to find out what are the differences and similarities between the two educations. It also aims to look at other important aspects using the lens of Islamic Education. This research is qualitative in nature by sifting and analyzing various literature be it books, articles or other sources. This research uses the comparative method to analyze the similarities and differences between the two. This research also tries to look at the two educational bases from another point of view, namely using the lens of Islamic Education. As a result, it turns out that there is one important aspect that is forgotten, namely the development of student character. The development builds spiritual values in students and tries to focus on self-improvement.